Sex-dependent alterations of colonic epithelial permeability: relevance to irritable bowel syndrome - Larauche, Muriel; Mahurkar-Joshi, Swapna; Biraud, Mandy; Ju, Tiffany; Mayer, Emeran A.; Chang, Lin (Frontiers in Physiology, 2025)
IntroductionIncreased intestinal permeability is a possible pathophysiological mechanism of irritable bowel syndrome (IBS). Increased colonic epithelial permeability is associated with visceral nociception in rodents and abdominal pain severity in IBS patients. Although IBS is more common in women, most studies on IBS-associated epithelial dysfunction have largely overlooked sex as a biologic variable.MethodsMen and women with Rome III- and Rome IV-positive IBS and HCs rated GI symptoms including abdominal pain severity at baseline, 24 h prior and immediately post procedure. Epithelial function was assessed ex vivo in Ussing chambers using sigmoid colon biopsies, by monitoring short-circuit current (Isc), transepithelial electrical resistance (TEER) and mucosal permeability to FITC-dextran 4 kDa (FD4). Biopsies tight junction protein mRNA expression was assessed using RNA seq. Statistical analyses included a framework of General Linear Models and linear contrast analyses performed using R software.Results44 IBS patients (66% women, 30 years) and 19 HCs (53% women, 28 years) were enrolled. The proportion of women was not different between groups. As a group, IBS patients exhibited lower TEER compared to HCs (16.9 ± 5.5 vs. 21.5 ± 6.5 Ω/cm2, p = 0.01, FDR = 0.02), but no difference in FD4 serosal concentration or Isc (basal or stimulated). Within men, IBS had lower TEER vs. HCs, but there was no disease difference within women. Independent of diagnosis, women had 1.3-fold lower TEER concentration and 1.5-fold higher FD4 serosal concentration than men. These sex differences were also seen within HCs, although within IBS, FD4 permeability only showed a trend to be higher in women vs. men. Abdominal pain ratings and IBS severity scores were not associated with TEER or FD4 concentration.DiscussionOur study confirms prior reports that IBS patients demonstrate altered sigmoid colonic epithelial function and shows for the first time that these are independent of sex. However, sex differences in sigmoid colonic epithelial function are observed independently of disease status. Further studies are needed to delineate if intestinal permeability interacts with other factors in the pathophysiology of IBS and if these interactions differ by sex.